Analisis Praktik Corporate Social Responsibility (CSR) Selama Pandemi Covid-19 pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Sari, Nurma; Sari, Maemunah Nurmaya (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research aims to find out what efforts companies have made through their CSR programs during the Covid-19 pandemic. The approach in this research is a qualitative approach, and this research is website-based research, where all the data is mostly taken from internet sources, especially from the website www.idx.co.id. The companies that make up the population in this research are 152 companies from two sectors and the annual reports observed are in 2020, due to the limited data obtained, namely there are no 2020 and 2021 annual reports on the Indonesian Stock Exchange companies. The research results show that as of August 2022, of the 152 companies studied there were only 3 companies that made 2020 annual reports. From the CSR reports used as research samples, researchers drew the conclusion that the CSR practices carried out by companies during the Covid-19 pandemic were classified into 3 groups, namely CSR activities for employees, for the community, and thirdly for customers. Researchers also concluded that the CSR report of PT Surya Permata Andalan Tbk. is superior in terms of expressing health insurance for employees, while PT Selamat Selamat is superior in terms of disclosing the nominal amount of CSR funds spent.